Quantum Physics : Concepts and Applications - Lee,Jenson (New York : Larsen and Keller, 2023)
Quantum physics is a branch of science that focuses on quantum mechanics, which seeks to explain the behavior of matter and energy. Some of the major concepts within this field are superposition, wave-particle duality and uncertainty principle. Superposition refers to the phenomena of an object existing as a combination of multiple possible states simultaneously. The uncertainty principle is a mathematical concept which states that it is impossible to know the position and velocity of an object at the same time, regardless of the method used for measurement. The wave-particle duality describes the behavior of light and matter wherein it behaves as a wave or a particle depending on the method of measurement. The book aims to shed light on quantum physics and the recent researches in this field. From theories to research to practical applications, studies related to all contemporary topics of relevance to this field have been included herein. The book is a vital tool for all researching and studying this area of phyiscs.
Keywords: quantam -- Physics